2021
DOI: 10.1080/20009666.2021.1948669
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine infusion as a sedative-analgesic in severe ARDS (KISS)

Abstract: RationaleKetamine has been used as a sedative analgesic in trauma setting, but data regarding its efficacy and safety is lacking in severe ARDS. This retrospective study aims to determine if Ketamine is safer as a sedative agent in mechanically ventilated patients. During the COVID pandemic, as there was a shortage of sedative agents, Ketamine was used. ObjectivesThe primary objective was to compare the safety of ketamine to other sedatives. The secondary objective was to compare the effect of ketamine to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
(15 reference statements)
2
5
1
Order By: Relevance
“…Similar to our finding, Pata ( Pata et al, 2021 ) and his colleagues found that patients who were sedated with ketamine had a lower incidence of hospital-acquired infection. This can be explained by the immunomodulatory activity of ketamine; it has been shown to antagonize inflammatory responses and reduce proinflammatory cytokine production, such as reduced IL-6 and TNFα production ( Yuhas et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to our finding, Pata ( Pata et al, 2021 ) and his colleagues found that patients who were sedated with ketamine had a lower incidence of hospital-acquired infection. This can be explained by the immunomodulatory activity of ketamine; it has been shown to antagonize inflammatory responses and reduce proinflammatory cytokine production, such as reduced IL-6 and TNFα production ( Yuhas et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another factor that might have contributed to our findings of shorter length of hospital stay could be related to reduced incidence of delirium with low doses of ketamine ( Perbet et al, 2018 ). These results were inconsistent with the results of the Pata et al ( Pata et al, 2021 ) study, which reported that patients in the ketamine group had longer hospital stays due to neurocognitive perturbation.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Pata et al, in their retrospective cohort study, recognised that these sedation challenges exist and demonstrated safety and reduced mortality with ketamine in severe ARDS COVID patients. 24 Our study cohort represents a historic population of COVID-19 critically ill patients with data obtained during the early period of the pandemic, prior to immunisation and established therapies being validated; thus, the severity of respiratory failure and ARDS along with the disease burden was high. In our enterprise, ketamine was added when the sedation and analgesia requirements exceeded what was possible with maximal doses of other agents.…”
Section: Discussionmentioning
confidence: 99%